Elementary Preservice Teacher Field Supervision: A Survey of Teacher Education Programs. (3rd May 2017) - Jacobs, Jennifer; Hogarty, Kristine; Burns, Rebecca West
ABSTRACT: There is a heightened focus within teacher education to centralize clinical experiences and develop strong partnerships between schools and universities. University field supervisors fulfill a critical role within clinical experiences because they are uniquely situated in spaces where they can help preservice teachers and school-based partners integrate theory and practice. However, historically, field supervision has been devalued within teacher education programs. The purpose of this research was to gain insight into how various teacher education programs are actualizing field experiences and specifically field supervision within this time of reform in teacher education. This survey explored the question, "What is the state of preservice teacher field supervision within elementary teacher education programs?" Findings from this study suggest teacher education programs surveyed are positioned to respond to reforms in the areas of enacting multiple field experiences as well as conceptualizing field supervision beyond observation and feedback. Findings can help teacher education programs begin to develop common understandings, goals, and nomenclature about actualizing reforms for clinically-rich teacher education.